Recovery of hydrothermal vent communities in response to an induced disturbance at the Lucky Strike vent field (Mid-Atlantic Ridge). (June 2021) - Marticorena, J.; Matabos, M.; Ramirez-Llodra, E.; Cathalot, C.; Laes-Huon, A.; Leroux, R.; Hourdez, S.; Donval, J.-P.; Sarrazin, J.
Abstract: So far, the natural recovery of vent communities at large scales has only been evaluated at fast spreading centers, by monitoring faunal recolonisation after volcanic eruptions. However, at slow spreading ridges, opportunities to observe natural disturbances are rare, the overall hydrothermal system being more stable. In this study, we implemented a novel experimental approach by inducing a small-scale disturbance to assess the recovery potential of vent communities along the slow-spreading northern Mid-Atlantic Ridge (nMAR). We followed the recovery patterns of thirteen Bathymodiolus azoricus mussel assemblages colonising an active vent edifice at the Lucky Strike vent field, in relation to environmental conditions and assessed the role of biotic interactions in recolonisation dynamics. Within 2 years after the disturbance, almost all taxonomic richness had recovered, with the exception of a few low occurrence species. However, we observed only a partial recovery of faunal densities and a major change in faunal composition characterised by an increase in abundance of gastropod species, which are hypothesised to be the pioneer colonists of these habitats. Although not significant, our results suggest a potential role of mobile predators in early-colonisation stages. A model of post-disturbance succession for nMAR vent communities from habitat opening to climax assemblages is proposed, also highlighting numerous knowledge gaps. This type of experimental approach, combined with dispersal and connectivity analyses, will contribute to fully assess the resilience of active vent communities after a major disturbance, especially along slow spreading centers targeted for seafloor massive sulphide extraction. Graphical abstract: Image 1 Highlights: Novel experimental approach by inducing small-scale disturbance to assess the recovery of vent communities. Full recovery of faunal taxonomic richness within 2 years after the disturbance. Incomplete recovery of faunal densities and enhancement of species evenness in post-disturbance communities. Gastropod species appears to be the pioneer colonists of active vent assemblages. There are differences in the recovery rate of active vent in comparison to peripheral area and inactive structure.